Phenytoin and Cognitive-Motor Performance - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Cognitive-motor function in 51 children with seizures well controlled with phenytoin (PHT) monotherapy was assessed in relation to drug concentration, seizure type, and time of medication at the Departments of Psychiatry and Pharmacology, Auckland University School of Medicine, Australia.